2007
DOI: 10.1177/0306624x07299304
|View full text |Cite
|
Sign up to set email alerts
|

Female Recidivists Speak About Their Experience in Drug Court While Engaging in Appreciative Inquiry

Abstract: Eleven female drug-court participants looked at current and past experiences to assess their program and envision future program innovations. From these women's perspective, the strongest component of drug court was being surrounded by staff dedicated to their progress and recovery. Graduated supervision and accurate drug testing were appreciated rather than resented when the participants were not humiliated and were treated with respect. Wraparound services, resources, and referral; treatment facilities that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 16 publications
0
58
0
Order By: Relevance
“…Two were published as dissertations (Kerr, 2009; Mastrorilli, 2008), and the remaining three appeared in peer-reviewed journals (Fischer, Geiger, & Hughes, 2007; McKim, 2008; Sowards, O’Boyle, & Weissman, 2006). In keeping with the aim of this review, the purpose of these investigations was to examine the attributes of substance abuse programs that were specifically designed for women who were referred through the criminal justice system to participate in treatment outside of high-security prisons or jails.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two were published as dissertations (Kerr, 2009; Mastrorilli, 2008), and the remaining three appeared in peer-reviewed journals (Fischer, Geiger, & Hughes, 2007; McKim, 2008; Sowards, O’Boyle, & Weissman, 2006). In keeping with the aim of this review, the purpose of these investigations was to examine the attributes of substance abuse programs that were specifically designed for women who were referred through the criminal justice system to participate in treatment outside of high-security prisons or jails.…”
Section: Resultsmentioning
confidence: 99%
“…One program was classified as a drug court and served as an alternative to incarceration (Fischer et al, 2007). Two were community-based outpatient programs that provided services for women who were mandated to participate in treatment through the criminal justice system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, participants were generally more critical of their drug court programs compared with participants in the current study (Fischer et al, 2007;Fulkerson et al, 2012;Roberts & Wolfer, 2011;Wolfer, 2006). The previous study revealed the least critical feedback from participants was one in which participants had been in the program for at least 7 months and were in Phase 2 or 3 of the program (Fischer et al, 2007). Further studies are needed to learn more about how time affects participants' ability to reflect on their experiences.…”
Section: Conclusion and Future Researchmentioning
confidence: 53%
“…Findings demonstrated that the most important factors for drug court success were caring staff, supportive and fair judge, being treated with respect by drug court team, and treatment that focused on increasing independence and responsibility. Several women indicated they had survived traumatic events and found it helpful to have female counselors with whom to discuss these experiences (Fischer et al, 2007). Three problematic areas included equal treatment of drug and house-rule violations, losing children as a result of entering treatment, and lack of inclusion in decision making with regard to their treatment program.…”
Section: Qualitative Findings On Drug Courtsmentioning
confidence: 99%